2009
DOI: 10.1001/jama.2009.289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Response to Attenuated Tissue-Cultured Smallpox Vaccine LC16m8

Abstract: HE THREAT OF SMALLPOX BIOterrorism has prompted reconsideration of the need for smallpox vaccination. 1-3 Serious adverse events associated with firstgeneration vaccines such as the New York City Board of Health (Dryvax; Wyeth, Madison, New Jersey), Lister, and Ikeda strains 4-8 have raised obstacles to vaccination campaigns in the United States. 7-9 Second-generation vaccines such as ACAM2000 (Acambis, Cambridge, Massachusetts) that use a first-generation seed virus but are grown in tissue culture are also us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 25 publications
(20 reference statements)
4
60
1
3
Order By: Relevance
“…114,115 Other attenuated replication competent vectors are M65 and M101, derived from the Western Reserve (WR) strain after multiple passages in Friend erytroleukemia cells, that have been shown to contain mutations in multiple gene sequences but with the capacity to trigger immunogenicity and protection against leishmania parasitic infection. 116 Another replication-competent and attenuated smallpox-derived vaccines, such as the Japanese LC16m8 (derived from the Lister vaccinia strain), [117][118][119] and the Chinese Tian-Tan strains 111,120,121 are also being investigated as vaccines for other diseases. Moreover, myxomavirus have been used as a promising vaccine candidate against several types of cancer, due to the oncolytic ability of this poxvirus to specifically infect various classes of human cancer cells.…”
Section: Enhancing Vector Replication Capacitymentioning
confidence: 99%
“…114,115 Other attenuated replication competent vectors are M65 and M101, derived from the Western Reserve (WR) strain after multiple passages in Friend erytroleukemia cells, that have been shown to contain mutations in multiple gene sequences but with the capacity to trigger immunogenicity and protection against leishmania parasitic infection. 116 Another replication-competent and attenuated smallpox-derived vaccines, such as the Japanese LC16m8 (derived from the Lister vaccinia strain), [117][118][119] and the Chinese Tian-Tan strains 111,120,121 are also being investigated as vaccines for other diseases. Moreover, myxomavirus have been used as a promising vaccine candidate against several types of cancer, due to the oncolytic ability of this poxvirus to specifically infect various classes of human cancer cells.…”
Section: Enhancing Vector Replication Capacitymentioning
confidence: 99%
“…These so-called vaccines of the third generation can induce a good immune response, and achieve high protection in animal experiments against highly pathogenic OPV. On the other hand, adverse effects of conventional vaccines can be widely ruled out [37][38][39][40][41][42]. In Japan, LC16m8 has recently obtained a marketing authorisation as vaccine from the national authority.…”
Section: Pdf)mentioning
confidence: 99%
“…It must be noted that LC16m8 was licensed as vaccine in Japan. The extent to which MVA or derivatives of MVA will be licensed for prophylactic vaccination of humans also remains to be seen [39,42,110]. In this context, the clinical trial of the MVA vaccine IMVAMUNE in the USA has made the most progress [41,111].…”
Section: Therapy and Prophylaxismentioning
confidence: 99%
“…More recent clinical data suggest that LC16m8 has a better safety profile compared to the parental Lister strain. 69 In up-to-date preclinical studies LC16m8 vaccine was shown to induce levels of immunity very comparable to those elicited with Dryvax vaccine eradication campaign because of a better safety record than other vaccines based on VACV strains Copenhagen or Bern. 5 These first generation vaccines were produced by several countries on various tissues: e.g., Lister based vaccines were produced on chick chorioallantoic membranes while NYCBH was propagated on calf or water buffalo skin and stored either as wet frozen vaccine or later on as dried stock (Dryvax).…”
Section: The Different Generations Of Vaccinesmentioning
confidence: 99%